In Silico Studies and Admet Predictions Diterpenoid Compound Andrographis paniculata (Burm.f.) Nees as Inhibitor of Streptococcus mutans - Nurfadillah, Arafah; Amir, Nur Insani; Ramadhani, Sindi (Hayyan Journal, 2025)
Andrographis paniculata (Burm.f.) Nees are reported to have many bioactivities, including antibacterial, hepatoprotective, antimalarial, antihypertensive, antipyretic, antithrombolytic, and other pharmacological effects. This study aims to determine the benefits of the active compound Andrographis paniculata in inhibiting the activity of the enzyme glucosyltransferase. This research method was carried out in silico on 3AIC receptors using Chimera, ChemDraw Ultra 12.0, MGLtools, Autodock4, Biovia Discovery Studio, and Toxtree software. The results showed that of the 12 test compounds, the AP11 compound has the lowest ∆G free bond energy of -8.5KKal/mol, lower than natural ligands, and more hydrogen bonds than natural ligands, MES. Therefore, it can be concluded that the AP11 compound has the most potential to inhibit glucosyltransferase receptors